1995
DOI: 10.1007/bf02564763
|View full text |Cite
|
Sign up to set email alerts
|

Perineal ultrasonography in postoperative assessment of two different surgical procedures for stress urinary incontinence

Abstract: Thirty-eight incontinent and 57 continent patients who had undergone MMK urethropexy and anterior colporrhaphy procedures were examined by perineal ultrasonography. Bladder neck hypermobility was described with ventrodorsal and cephalocaudal directional parameters. In the incontinent patients both cephalocaudal and ventrodorsal mobilities were found to be significantly greater compared to the continent group, the latter ultrasonographic parameter being relatively more significant (P < 0.01 and P < 0.001, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…The mobility of the UVJ during stress is evaluated unidirectionally or as two components in the cephalocaudal and ventrodorsal directions. UVJ mobility is used most commonly as a criterion of SUI by most authors [19,24,25,[27][28][29][30][31]37,39,40,52] without taking any standard mobility measurement. A commonly accepted standard measurement of UVJ mobility is equal to or more than 1 cm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mobility of the UVJ during stress is evaluated unidirectionally or as two components in the cephalocaudal and ventrodorsal directions. UVJ mobility is used most commonly as a criterion of SUI by most authors [19,24,25,[27][28][29][30][31]37,39,40,52] without taking any standard mobility measurement. A commonly accepted standard measurement of UVJ mobility is equal to or more than 1 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Demirci et al [27] took a different approach using perineal ultrasonography compared to previous authors. Those that use perineal ultrasonography measure the movement of the UVJ in only one direction [19,23,25,26].…”
Section: Perineal Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Sowohl beim Miktionszysturethrogramm als auch beim TRUS ist die Möglichkeit der Beurteilung der urethralen Mobilität eingeschränkt. Darüber hinaus kann die im Rektum gelegene Sonde die Beweglichkeit des Blasenhalses beeinträchtigen und die Fähig-keit zum Pressen herabsetzen [12], sodass die Untersuchungsergebnisse möglicher-weise an Aussagekraft verlieren. Des Weiteren ist die Untersuchung für den Patienten unangenehm und bisweilen schmerzhaft.…”
Section: Diskussionunclassified
“…Ultrasonography has been used for postoperative evaluation of patients to document the reasons of failed operations (4–7). These evaluations suggested that patients with successful operations had beneficial stabilization of the bladder necks by surgical repair, while those with persistent or recurrent incontinence were associated with reacquisition of the bladder neck hypermobility (4–9). Although, several different measurement methods have been proposed to objectively document the position or the mobility of the bladder neck, the effectiveness of these methods was controversial (4–13).…”
mentioning
confidence: 99%